Management Strategy in Public Services at the Civil Registry Office - Rasmika, Rasmika; Mujahid, Mujahid; Suyuthi, Nurmadhani Fitri (Newinera Publisher, 2023)
This study aims to analyse management strategies in public service at the Dukcapil Office of Penajam Paser Utara Regency. The focus of this research is to evaluate the strategies implemented to enhance the quality and efficiency of public services related to population registration, civil registration, and data management. Understanding these strategies is expected to provide valuable recommendations for improving services in the future. The research employs a qualitative approach, conducting in-depth interviews with key informants including the Head of Data Utilization and Service Innovation, the Head of Population Registration, the Head of Civil Registration, the Head of Population Administration Information Management, and members of the general public. Data were collected through interviews and direct observation. Data analysis was performed using interactive model techniques, allowing for comprehensive insight and understanding of the applied management strategies. The results reveal that the Dukcapil Office of Penajam Paser Utara Regency has implemented a comprehensive management strategy in public service. Thorough planning, including the integration of technology and online systems, facilitates highly efficient population registration and civil registration processes. Effective organization ensures that human resources and technology are well-managed to achieve service goals. Guidance through training and simulations ensures that staff perform their duties competently. Control is exercised by monitoring and evaluating systems and staff performance to maintain service quality. These strategies have enhanced the quality and efficiency of public services, providing greater convenience and trust to the public in the administration of population and civil registration in Penajam Paser Utara Regency.